The economic impact of COVID-19 in Iceland : how did COVID-19 affect the economic growth in Iceland? - Nikulás Torfi Guðmundsson 1998-; Óskar Arnarsson 1999- (2022)
COVID-19 had a significant impact on the Icelandic economy. We looked at substantial and credible data on Iceland's GDP factors to assess how hard the virus hit the economy. Consumption, investment, government expenditure, exports, and imports are all variables that construct Iceland’s gross domestic product, giving us a better insight on how the economy is coping with the plague. Consumption and consumer pattern changed when Icelanders were mandated to stay at home and not socialise unless it was digitally. The most significant change occurred in the hotel and restaurant industry. However, consumption in Iceland recovered swiftly because of individuals adjusting their consumption patterns; internal travel surged after the outbreak. Investment fell in 2020 but increased dramatically in 2021 owing to the construction of new structures. Government expenditure was the sole determinant of Iceland's GDP that did not decline during COVID-19. This comes as no surprise considering the importance of the government assisting infrastructure, particularly hospitals, in the face of a pandemic. Because of the pandemic's impact on tourism, the COVID-19 pandemic had the largest impact on Iceland's exports. Because tourism makes for a major portion of total export income, the downturn in tourism was felt more acutely in Iceland than in most other countries. However, with the pandemic gradually diminishing, foreign travel is becoming more popular, and the tourist sector is regaining its foundation. Import growth in Iceland is largely driven by changes in private consumption and corporate investment. Imports declined dramatically in 2020, owing mostly to lower service imports as Icelanders go abroad less often. With 81% of the nation's population over the age of 5 now vaccinated, individuals are more eager to travel overseas, and therefore imports are returning to pre-pandemic levels. People's life will be altered if a worldwide pandemic strikes their economy. As the epidemic consumed more and more of Iceland's sectors, the ...